Condiciones de alimentación, hábitat y salud en el bienestar de los felinos del Parque Turístico de Quistococha, Iquitos. Loreto. 2025 - Soplin Ramirez, Genessis Karina (2025)
A descriptive, non-experimental, cross-sectional study characterized the feeding, habitat, and health conditions that impact the well-being of captive felines in Quistococha Tourist Park. Convenience sampling was used with 10 Amazonian felines and 5 staff members responsible for their care. Systematic direct observation and semi-structured interviews were conducted; the instruments were validated (Cronbach's alpha = 0.757). Descriptive statistics, the Shapiro-Wilk test, and Spearman's correlation coefficient were used. The results show that the assessed conditions directly impact the felines' well-being. There have been improvements in feeding and emergency medical care, but deficiencies persist in the health plan and enclosure design. Staff consider the diet adequate in terms of frequency and quality, although nutritional differences are detected between individuals, suggesting the need for individualized dietary monitoring. The facilities offer acceptable cleanliness, shade, and shelter, but have limited space and structural safety, which impairs natural behavior. Although most cats show signs of good health, some show signs of stress or physical deterioration. Implementing environmental enrichment strategies and ongoing behavioral monitoring is recommended. These actions will contribute to sustainably improving the physical, behavioral, and emotional well-being of cats in captivity.